2021
DOI: 10.1108/gm-10-2019-0182
|View full text |Cite
|
Sign up to set email alerts
|

“Like will to like” or “opposites attract”? Management board diversity affects employer attractiveness

Abstract: Purpose How diversity in management boards affects employer attractiveness has yet to be fully clarified. This paper aims to contrast the two main theoretical rationales – similarity attraction and diversity attraction – and examines whether potential employees are more attracted to an organization with a homogenous board (in terms of gender and ethnicity) or to an organization with a diverse board. Design/methodology/approach Participants (N = 629) were simultaneously presented with two pictures of manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 109 publications
(135 reference statements)
0
14
0
Order By: Relevance
“…Since job applicants seek a work environment that shares their values (Schreurs et al, 2009), the diversity climate prevailing in the company might mainly affect people who attach importance to a diverse work environment (Avery et al, 2013). In contrast, other studies find no moderating effect of attitudes regarding diversity on attractiveness (Schäpers et al, 2021). Again, future studies are needed to identify possible moderators.…”
Section: Limitations and Future Researchmentioning
confidence: 97%
See 3 more Smart Citations
“…Since job applicants seek a work environment that shares their values (Schreurs et al, 2009), the diversity climate prevailing in the company might mainly affect people who attach importance to a diverse work environment (Avery et al, 2013). In contrast, other studies find no moderating effect of attitudes regarding diversity on attractiveness (Schäpers et al, 2021). Again, future studies are needed to identify possible moderators.…”
Section: Limitations and Future Researchmentioning
confidence: 97%
“…This includes managing and promoting diversity. For example, Schäpers et al (2021) showed that people perceive a gender-diverse board as more attractive than a homogeneously male or a homogeneously female board. In line with this, a positive diversity climate improves workrelated engagement, job performance and job satisfaction (McKay et al, 2008).…”
Section: Diversity and Employer Attractivenessmentioning
confidence: 99%
See 2 more Smart Citations
“…The second most analyzed topic is the relationship between women’s presence on corporate boards and corporate social responsibility (Biswas et al , 2021; Dang et al , 2021; Mansoor and Ali, 2018). Other studies analyzed the boards’ strategic control (Nielsen and Huse, 2010), corporate sustainability (Galbreath, 2011), corporate governance (Abdullah et al , 2016), efficiency (Ramly et al , 2017), corporate reputation (Inamdar and Nagendra, 2017), corporate environmental actions (Gong et al , 2021), effects on agency costs (Amin et al , 2021), cost of debt (Kamil and Appiah, 2021), adoption of the United Nations Sustainable Development Goals (Cicchiello et al , 2021) and employer attractiveness (Schäpers et al , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%